Telomere length in mantle cell lymphoma - Jebaraj, Billy Michael Chelliah; Kienle, Dirk Lars; Lechel, André; Mertens, Daniel; Heuberger, Maria; Ott, German; Rosenwald, Andreas; Barth, Thomas F. E.; Möller, Peter; Zenz, Thorsten; Döhner, Hartmut; Stilgenbauer, Stephan (Blood, 2013)
Telomere shortening is of pathogenic and prognostic importance in cancers. In the present study, we analyzed telomere length in 73 mantle cell lymphoma (MCL), 55 chronic lymphocytic leukemia (CLL), and 20 normal B-cell samples using quantitative PCR (Q-PCR) to study its association with disease characteristics and outcome. Telomere length was found to be highly variable in MCL (range, 2.2-13.8 kb; median, 4.3 kb). Telomere dysfunction in MCL was evident from comparison with normal B cells (median, 7.5 kb), but had no significant association with any biologic or clinical feature. This was in contrast to CLL, in which a significant correlation of short telomeres with poor prognostic subgroups was confirmed. There was a trend toward an increased number of genomic aberrations with shortening of telomeres in MCL. No difference in survival was observed between the groups with short and long telomeres, indicating that, as opposed to CLL, telomere length is not of prognostic relevance in MCL.
Gesehen am 26.03.2021